APLIKASI STATISTIK DESKRIPTIF: POLA KONSUMSI MAHASISWA PADA BUAH DAN OLAHANNYA SAAT PANDEMI COVID-19 - Rasmikayati, Elly; Rochdiani, Dini; Saefudin, Bobby Rachmat (Universitas Galuh, 2023)
During the Covid-19 pandemic outbreak around the world, it was very important for students to increase their consumption of fruit and processed foods to boost their immunity. Even though fruit and its preparations have various benefits that can maintain the body's immunity during the Covid-19 pandemic, students are often lacking in terms of the amount and frequency of consuming these types of food. The purpose of this study is to describe the pattern of consumption of fruit and its preparations among students during the Covid-19 pandemic and to identify the obstacles faced by students in consuming fruit and its preparations. This study uses a quantitative design. The data analysis technique used is descriptive analysis. The research was conducted on students majoring in Agribusiness and Agrotechnology, Faculty of Agriculture, Padjadjaran University class of 2019. The results showed that more respondents were female, lived at home, had an allowance of less than or equal to IDR 500,000, had monthly expenses of more than IDR 150,000, number of members family between 4-5 people and college parents education. The frequency of fruit and processed fruit consumption by students is in the sufficient category, namely at least 1 time/day, which is 29%. Approximately 25% of students consume fruit and its processed products, which are in the sufficient category, namely at least 150 grams/day. The majority of students have problems in consuming fruit and its processed products, namely being lazy to cut fruit and lazy to make processed fruit.